Acute effect of resistance training volume on hormonal responses in trained men - Leite, R. D.; Prestes, J.; Rosa, C.; de Salles, B. F.; Maior, A.; Miranda, H.; Simão, R. (The Journal of Sports Medicine and Physical Fitness, 2011)
volumes. The first protocol consisted of 3 sets at 80% of 6 RM and the second protocol was 3 sets at 80% of 12 RM with 2 minutes rest between sets and exercises, separated by seven days between them. The exercise order used was: barbell bench press, leg press, machine front lat-pull down, leg curl, shoulder abduction and leg extension. The blood variables analyzed were: testosterone, growth hormone (GH), cortisol and testosterone/cortisol ratio (T:C) before (Pre) and immediately after (Post) each exercise session. RESULTS: The intra-groups comparison for testosterone and hGH revealed a significant increase in 80%-6RM and 80%-12RM. Cortisol levels was significantly higher in 80%-12RM and T:C ratio in 80% 6 RM when compared Pre and Post values. Inter-groups comparison showed higher hGH and cortisol levels and lower T:C ratio for 80% 12 RM. There was no statistically significant different between 80%-6RM and 80%-12RM for testosterone. CONCLUSION:The present study confirms that the volume of resistance training can be an important factor in the modulation of acute hormonal responses.